2019
DOI: 10.3389/fmed.2019.00135
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Tuberculosis Outcomes With a Combined Medical and Social Approach

Abstract: Setting: Studies performed locally in Switzerland in the late eighties reported unsatisfactory treatment outcomes. Better outcomes were observed since the introduction of directly observed therapy (DOT) in the late nineties and improvement in social support in recent years. Design: retrospective study of treatment outcomes for all tuberculosis (TB) patients notified in Vaud County (VD), Switzerland, between, 1st of January 2010 and 31st of December of 2014. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The relative scarcity of studies on these rural-to-urban migrants is possibly due to insufficiently recorded residency status outside of countries with strong central planning and unitary political systems, such as China and Viet Nam, where institutionalized household registration systems (hokuo and ho khau, respectively) can facilitate identification and segmentation of the general population into these subgroups. However, even in the absence of clear denomination mechanisms, studies from developed countries have shown the effectiveness of social support in improving TB treatment outcomes among migrants [48]. Nevertheless, more evidence is needed to address potential barriers to economic migrants in registering residency, gaining full access to locally available public services and overcoming the risk inequalities in this subpopulation tied to social determinants of health.…”
Section: Discussionmentioning
confidence: 99%
“…The relative scarcity of studies on these rural-to-urban migrants is possibly due to insufficiently recorded residency status outside of countries with strong central planning and unitary political systems, such as China and Viet Nam, where institutionalized household registration systems (hokuo and ho khau, respectively) can facilitate identification and segmentation of the general population into these subgroups. However, even in the absence of clear denomination mechanisms, studies from developed countries have shown the effectiveness of social support in improving TB treatment outcomes among migrants [48]. Nevertheless, more evidence is needed to address potential barriers to economic migrants in registering residency, gaining full access to locally available public services and overcoming the risk inequalities in this subpopulation tied to social determinants of health.…”
Section: Discussionmentioning
confidence: 99%
“…According to the WHO and European Respiratory Society recommendations for TB prevention programmes in industrialized countries with low TB incidence, contact investigation should be performed for all contagious pulmonary TB to reduce the transmission of the disease [20]. The Vaud Pulmonary League organizes and implements community-based surveys following a new TB diagnostic using, when necessary, an active detection strategy that allows the detection of latent TB or the discovery of individuals with secondary active TB [18]. However, epidemiological investigations are sometime unable to discriminate between multiple circulating clusters and it is sometime necessary to rely on available M. tuberculosis strains genotyping to support or to disprove the hypothesis of recent transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The different views and perspectives of the patients and their families, shared during these meetings, helps to build connections and to coordinate the different procedures, facilitate treatment supervision and contact investigations, and eventually permits identification of some gaps. This article also shows that these providers are not only delivering care to an individual patient with TB, but they are assuming an important public health function that entails a high level of responsibility to the community, as well as to the individual patient [18]. Hence, molecular epidemiological investigations could add value to contact-tracing investigations but do not replace clinic epidemiological efforts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The legitimacy of pre-migration TB screening has been questioned, [59,60] with some arguing that better primary care should be available for migrants to support their general health and wellbeing, as well as early TB identification. Patient-centered approaches to TB care have been shown to reduce diagnostic delay, with likely reduction in TB transmission, and improve treatment outcome in migrants [61]. We explore some of the tensions between the classic public health and social dimensions of the problem, as well as the resultant ethical dilemmas in greater detail.…”
Section: Ltbi Screeningmentioning
confidence: 99%